Experience of Routine Live-birth Screening for Galactosaemia in a British Hospital, with Emphasis on Heterozygote Detection. Issue 251 (February 1972) - Ellis, Graham; Wilcock, A. Ross; Goldberg, David M.
Abstract : Results are reported of a screening programme for galactosaemia covering a period of 2½ years and 6415 births. The gene frequency for galactosaemia estimated from the data of the screening programme was 0·002. This conflicted with the known live-birth incidence of at least 1: 50, 000 during this same period. 2 of the 4 galactosaemic infants concerned died under circumstances that were preventable had they been screened at birth. The need to screen all sick infants for galactosaemia is emphasized, as is the requirement for reliable information on its incidence in Great Britain. The screening test employed (Beutler and Baluda, 1966a) seemed appropriate for this purpose. It was simple to perform and apparently accurate in galactosaemic infants. Its accuracy in detecting heterozygotes is uncertain. This test should be available in all hospitals receiving sick neonates.